Noodweere: A Challenge of Justice for Investigators - Sadarudin Babuta (Universitas Negeri Gorontalo, 2023)
This study aims to analyze the primary considerations for the police to determine the victim of abuse as a suspect in a crime related to noodweer, as well as to examine the legal remedies that can be taken in determining him as a suspect for the alleged crime of persecution that was carried out by force. This type of research is normative-empirical legal research. The approach used is the Statute Approach; and the case approach. The results of the research show that the primary considerations of investigators in determining someone to become a suspect, even if the person concerned is a victim in the crime of persecution, are determined by the results of the visum et repertum and two sufficient pieces of evidence and two witnesses. A person who is arrested/detained after being named as a suspect, can carry out a pre-trial if the act of arrest/detention is deemed illegal, and violates the provisions of the applicable laws and regulations.